Vehicle Dynamics Simulation in Matlab/Simulink Environment - Szántó, András; Hajdu, Sándor (International Journal of Engineering and Management Sciences, 2018)
In the following we are researching different methods of vehicle dynamics simulations. Starting from a simple two-wheeled vehicle model, we are showing ways to simulate the movement of vehicles with real suspensions on any surfaces. MATLAB, Simulink and Simscape provide very suitable resources for the above mentioned purposes. The benefits of such vehicle model become obvious because of the fact during the physics simulation we can access all the data we need to simulate any control algorithms for vehicles: in this article we are presenting a simple ABS control simulation.